PENENTUAN AWAL DAN AKHIR BULAN RAMADAN DENGAN METODE HISAB “URF KHOMASI” DI PESANTREN MAHFILUDDUROR JEMBER - Hanip, Abdul (Program Studi Hukum Keluarga Islam, 2023)
Determination of the beginning of the Kamariah month is one of several branches of astrology that often causes problems. This is due to the use of different methods of determining the beginning of the month. Nowadays, there are many contemporary hisab theories that are more up to date with astronomy. However, in practice there are still many groups that use hisab 'urfi as the basis for determining the beginning of the Kamariah month, especially for determining the beginning of Ramadan and Shawwal. Hisab 'urfi is a calculation method based on the average circulation of the Moon around the Earth, with inaccurate calculation results because it does not pay attention to other astronomical factors. One of the groups that still use the 'urfi hyssab is the Khomasi 'urfi hyssab user at the Mahfilud Duror Islamic Boarding School, Suger Kidul Village, Jelbuk District, Jember Regency. Many contemporary hisab methods that have sprung up and unification efforts by the Government do not make Khomasi 'urfi hisab users budge. They still persist with what they believe so far.